2013
DOI: 10.5194/acp-13-5813-2013
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and fine particle in the western Yangtze River Delta: an overview of 1 yr data at the SORPES station

Abstract: This work presents an overview of 1 yr measurements of ozone (O3) and fine particular matter (PM2.5) and related trace gases at a recently developed regional background site, the Station for Observing Regional Processes of the Earth System (SORPES), in the western part of the Yangtze River Delta (YRD) in eastern China. Ozone and PM2.5 showed strong seasonal cycles but with contrast patterns: O3 reached a maximum in warm seasons but PM2.5 in cold seasons. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
252
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(278 citation statements)
references
References 49 publications
(47 reference statements)
14
252
1
Order By: Relevance
“…The decreases in those months can be explained by strongly absorbing aerosols from biomass burning or possibly industrial emissions. As Ding et al (2013a, b) and Wang and Zhang (2008) have reported, plumes from agricultural burning typically contain lightabsorbing carbonaceous aerosols, and these pollutants can seriously impair air quality. Indeed, aerosols from biomass burning were more than likely responsible for the low in SSAs found in our study during July and August.…”
Section: Aerosol Optical Properties: Single-scattering Albedomentioning
confidence: 99%
“…The decreases in those months can be explained by strongly absorbing aerosols from biomass burning or possibly industrial emissions. As Ding et al (2013a, b) and Wang and Zhang (2008) have reported, plumes from agricultural burning typically contain lightabsorbing carbonaceous aerosols, and these pollutants can seriously impair air quality. Indeed, aerosols from biomass burning were more than likely responsible for the low in SSAs found in our study during July and August.…”
Section: Aerosol Optical Properties: Single-scattering Albedomentioning
confidence: 99%
“…The Yangtze River Delta (YRD) is characterized by a variable aerosol composition and increasing aerosol concentration during the last two decades (Ding et al, 2013a;Qi et al, 2015). Using multi-sensor retrievals, this study aims to systematically examine the response of warm cloud parameters (CDR, CF, COT and CTP) to the increase in the aerosol loading, where AOD is used as a proxy for CCN number con-Y.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements in Nanjing, for example, show 5 that reducing NO x emission could cause a tenfold increase in summer ozone concentrations. Reducing smog increases sunshine levels and temperatures, and alters rain and snowfall patterns 6 .…”
Section: Toxic MIXmentioning
confidence: 99%